2008
DOI: 10.1111/j.1464-410x.2008.07520.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of experience with Krzeski’s cystovaginoplasty for vaginal agenesis in Mayer‐Rokitansky‐Küster–Hauser syndrome: anatomical, histological, cytological and functional results

Abstract: RESULTSThe anatomical result was good in 37 patients during a mean (range) follow-up of 9 (0.25-19) years; the result was good in 30 patients, but seven developed vaginal stenosis that was successfully repaired. There were two cases of post-coital vesicovaginal fistula (VVF) at 18 months after CVP. Vaginal biopsies showed epithelialization of the posterior vaginal wall and gradual metaplastic changes from urothelium to stratified nonsquamous epithelium. Cytological smears showed a normal biphasic pattern and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…13 This similarity of neovagina to the normal one extended to include the epithelial lining. 14 Although most of studies reported a high success rate of Mc Indoe procedure to restore normal sexual function which varied from 75% in some series up to 100% in other studies, 15 yet none of them used a specific surveying scale to accurately assess the whole sexual satisfaction. 16 Instead of that, most of these studies relied only on the presence of lubrication and orgasm or absence of pain as an indicator of sexual function.…”
Section: Resultsmentioning
confidence: 99%
“…13 This similarity of neovagina to the normal one extended to include the epithelial lining. 14 Although most of studies reported a high success rate of Mc Indoe procedure to restore normal sexual function which varied from 75% in some series up to 100% in other studies, 15 yet none of them used a specific surveying scale to accurately assess the whole sexual satisfaction. 16 Instead of that, most of these studies relied only on the presence of lubrication and orgasm or absence of pain as an indicator of sexual function.…”
Section: Resultsmentioning
confidence: 99%
“…The neovaginal coating tissue normally requires a long period of time to acquire adequate elasticity, as the epidermal squamous layer needs to diminish its regenerative keratinization (31). Rejection of the skin graft (4%) as well as hair growth in the reconstructed tract has also been reported (31,33,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
“…Graft shrinkage, due to the development of granulomatous tissue (33), may cause neovaginal stenosis and dyspareunia. Lack of lubrication is also a problem when the neovagina is constructed with skin (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a risk of scarring which can cause stenosis, with resultant dyspareunia or apareunia (5). Inadvertent damage to bowel and bladder can occur, and vesicovaginal fistulae have been reported (5)(6)(7).…”
mentioning
confidence: 98%